Isochoric thermal conductivity of solid furan - Konstantinov, V.A.; Sagan, V.V.; Revyakin, V.P.; Zvonaryova, A.V.; Pursky, O.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Thermal conductivity of solid furan has been measured at isochoric conditions in the high-temperature orien-tationally-disordered phase I for samples of different densities. Our isochoric data show a gradual increase of ΛV with temperature whereas isobaric thermal conductivity goes down in this temperature range. The above effect is most clearly expressed in furan, where the atoms in the ring plane are not equivalent, as compared with earlier studied C6H6 and C6H12. The increase of ΛV with temperature can be attributed to weakening of the translation-al-orientational interaction which, in turn, leads to a decrease of phonon scattering on rotational excitations. The experimental data are described in terms of a modified Debye model of thermal conductivity with allowance for heat transfer by both low-frequency phonons and "diffuse" modes.